Policy Analysis of Strengthening Character Education in Realizing the Profile of Pancasila Students in Assisi Medan Private Primary School - Br Silaen, Pernanci; Abi, Antonius Remigius; Sinaga, Reflina; Juliana, Juliana; Florentina, Nova (Formosa Journal of Science and Technology, 2024)
Pancasila students are a way to encourage the birth of good human beings. How is the policy of strengthening character education in realizing Pancasila students in Assisi Medan Private Elementary School, with a sub-focus on the dimensions of faith, fear of God Almighty, and noble character. The purpose of this study is to find out and analyze how to realize religious morals, personal morals, morals to humans, morals to nature, and state morals. The method used in this study is a case study with data collection in the form of focused observation, in-depth interviews, and documentation. The results of the study explained that in realizing religious morals able to form a better person, personal morals can be implemented and applied to students so that students can uphold honesty and health that bolt students into formed characters, find that students and teachers can maintain harmony in the lives of fellow religious people, and respect the freedom to carry out worship according to their respective religions and beliefs,  Finding that health and hygiene is everyone's responsibility and in this school has stipulated that all who are in the school must maintain and care for nature to get good air and health and found that the morals of the country are also important to be instilled in students.